Analyzing the use of expert systems in improving the quality of decision-making - Mohammed Al-Mafrji, Ahmad Abdullah; Hamodi, Yaser Issam; Hassn, Sudad Gharib; Mohammed, Ahmed Burhan (Eastern-European Journal of Enterprise Technologies, 2023)
The success of institutions is in providing good services to customers through making various and strategic decisions as quickly and accurately as possible. Expert systems are important in making strategic decisions by improving the quality of decision-making. An expert system is an information system that relies on systems based on knowledge bases. It may also contain a knowledge base in a particular field and advanced programming methods that make a computer capable of thinking, deducing, and providing advice and expertise. This research aims to improve the period of time in decision making by using multiple experts systems and decision support system. The new system is implemented in MATLAB. For analyzing the proposed system, the data is collected by the questionnaire method and distributing 70 questionnaires to managers, heads of departments, employees, and those responsible for making various decisions in the institution under study. The valid questionnaires were 63. A questionnaire and the data were analyzed using the statistical program (SPSS). Based on the obtained data, the linguistic variables were created for the time period of the data, and the skills of the decision-maker as inputs for the proposed expert system, and a stage was added to the stages of the proposed expert system to diagnose the problem and set the goal to obtain the correct strategic decision. To obtain this advantage, let’s use expert systems compared to traditional methods of decision-making